A highly biocompatible bio-ink for 3D hydrogel scaffolds fabrication in the presence of living cells by two-photon polymerization. (15th June 2021) - Huang, Xing; Zhang, Yuxi; Shi, Mengquan; Zhang, Li-Peng; Zhang, Yunlong; Zhao, Yuxia
Graphical abstract: Highlights: A highly biocompatible bio-ink was prepared. 3D hydrogel scaffolds with L929 cells encapsulation were fabricated by 2PP. No apparent damage to L929 cells was observed within the laser-exposed region. L929 cells occupied the 3D scaffolds after 4 days incubation. Abstract: Bio-inks with living cells encapsulation are core materials for 3D printing of biomimetic cell culture models in vitro. In this study, a highly biocompatible bio-ink containing a hydrophilic benzylidene cyclopentanone photoinitiator (Y4) and a glycidyl methacrylate modified gelatin (Gel-GM) was prepared, and 3D hydrogel scaffolds with normal mouse fibroblast cells (L929) encapsulation were accurately fabricated by two-photon polymerization on a multiphoton confocal scanning laser microscopy. No apparent damage to L929 cells was observed within the laser-exposed region during the fabrication process. After four Days' incubation, the embedded L929 cells showed a vigorous proliferation and occupied most of the available space within the 3D hydrogel scaffolds, which indicated that the bio-ink would have great potential for 3D bioprinting.